Predictors of death among patients who completed tuberculosis treatment: a population-based cohort study. - Juan-Pablo Millet; Angels Orcau; Cristina Rius; Marti Casals; Patricia Garcia de Olalla; Antonio Moreno; Jeanne L Nelson; Joan A Caylà; Barcelona Tuberculosis Working Group (PLoS ONE, 2011)
BACKGROUND: Mortality among patients who complete tuberculosis (TB) treatment is still high among vulnerable populations. The objective of the study was to identify the probability of death and its predictive factors in a cohort of successfully treated TB patients. METHODS: A population-based retrospective longitudinal study was performed in Barcelona, Spain. All patients who successfully completed TB treatment with culture-confirmation and available drug susceptibility testing between 1995-1997 were retrospectively followed-up until December 31, 2005 by the Barcelona TB Control Program. Socio-demographic, clinical, microbiological and treatment variables were examined. Mortality, TB Program and AIDS registries were reviewed. Kaplan-Meier and a Cox regression methods with time-dependent covariates were used for the survival analysis, calculating the hazard ratio (HR) with 95% confidence intervals (CI). RESULTS: Among the 762 included patients, the median age was 36 years, 520 (68.2%) were male, 178 (23.4%) HIV-infected, and 208 (27.3%) were alcohol abusers. Of the 134 (17.6%) injecting drug users (IDU), 123 (91.8%) were HIV-infected. A total of 30 (3.9%) recurrences and 173 deaths (22.7%) occurred (mortality rate: 3.4/100 person-years of follow-up). The predictors of death were: age between 41-60 years old (HR: 3.5; CI:2.1-5.7), age greater than 60 years (HR: 14.6; CI:8.9-24), alcohol abuse (HR: 1.7; CI:1.2-2.4) and HIV-infected IDU (HR: 7.9; CI:4.7-13.3). CONCLUSIONS: The mortality rate among TB patients who completed treatment is associated with vulnerable populations such as the elderly, alcohol abusers, and HIV-infected IDU. We therefore need to fight against poverty, and promote and develop interventions and social policies directed towards these populations to improve their survival.